Mechanistic and synergistic actions of the in vitro antimycobacterial and immunomodulatory properties of Knowltonia vesicatoria (L.f.) Sims - Lall, Namrita (University of Pretoria, 2013)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2011.